Mechanisms of Adverse Local Tissue Reactions to Hip Implants - Eltit, Felipe; Wang, Qiong; Wang, Rizhi (Frontiers in Bioengineering and Biotechnology, 2019)
tract: Adverse Local Tissue Reactions (ALTRs) are one of the main causes of hip implant failures. Although the metal release from the implants is considered as a main aetiology, the mechanisms and the roles of the released products are topics of ongoing research. The alloys used in the hip implants are considered biocompatible and show negligible corrosion in the body environment under static conditions. However, modularity and its associated mechanically assisted corrosion have been shown to release metal species into the body fluids. ALTRs associated with metal release have been observed in hip implants with metal-on-metal articulation initially, and later with metal-on-polyethylene articulation, the most commonly used design in current hip replacement. The etiological factors in ALTRs have been the topics of many studies. One commonly accepted theory is that the interactions between the metal species and body proteins and cells generate a delayed type IV hypersensitivity reaction leading to ALTRs. However, lymphocyte reactions are not always observed in ALTRS, and the molecular mechanisms have not been clearly demonstrated. A more accepted mechanism is that cell damage generated by metal ions may trigger the secretion of cytokines leading to the inflammatory reactions observed in ALTRs. In this inflammatory environment, some patients would develop hypersensitivity that is associated with poor outcomes. Concerns over ALTRS have brought significant impact to both the clinical selection and development of hip implants. This review is focused on the mechanisms of ALTRs, specifically, the metal release process and the roles of the metal species released in the aetiology and pathogenesis of the disease. Hopefully, our presentation and discussion of this biological process from a material perspective could improve our current understanding on the ALTRs and provide useful guidance in developing preventive solutions.